Sulla ‘natura’ della legge: "nómos" come "ornamentum" - Šerpytytė, Rita (Filosofia, 2019)
The article raises the fundamental ontological question about what is the ‘true’ nature of the law. What is Law? The question is raised not theoretically, but situationally, that is, when you find yourself nowhere else but in the chapter Forma di legge of Giorgio Agamben’s book Homo Sacer. Here Agamben discusses the concept of law discussing Kafka’s legend Davanti alla legge and providing a critical analysis of its interpretations. In search of the answer to the question of the ‘nature’ of law, Kafka’s ‘open door’ metaphor is used. The article demonstrates that this metaphor, referring to the question of the ‘nature’ of law, refers figuratively to the formality of the law by questioning it. The key for finding an answer to this question seems to be given by Agamben’s concept of “state of exception”.